The Students’ Needs of Writing 3 Textbook - Endah Ratnaningsih; Candradewi Wahyu Anggraeni (Metathesis: Journal of English Language, Literature, and Teaching, 2017)
This research was aimed to describe students’ needs toward Writing 3 textbook. This was a case-study. The subjects of this research were the English Department students of Faculty of Education and Teachers’ Training of Tidar University. The data collection techniques used for knowing the students’ needs analysis in this research was taking questionnaires. The data analysis of this research was qualitative-descriptive. The result of this research is the description of students’ needs of Writing 3 textbook.Keywords – writing, textbook, students’ needs